Deserter - Itō, Junji, 1963- (Junji Ito story collection., 2021)
"A vengeful family hides an army deserter for eight years after the end of World War II, cocooning him in a false reality where the war never ended. A pair of girls look alike, but they're not twins. And a boy's nightmare threatens to spill out into the real world...A vengeful family hides an army deserter for eight years after the end of World War II, cocooning him in a false reality where the war never ended. A pair of girls look alike, but they're not twins. And a boy's nightmare threatens to spill out into the real world..."--Amazon.